Gathering data from health monitoring systems with Camel-K and Apache Kafka. - Koufoudakis, Alexandros (Manning Publications, 2021)
Remote health monitoring systems allow real-time gathering of health data, which later can be used to monitor the actual state of a patient, to prioritize patients, to come up with health recommendations, and to provide many other useful services of health care (e.g., telemedicine). Alexandros Koufoudakis focuses on how messages can be gathered from producers, enqueued by Apache Kafka, and finally consumed by a Camel-K integration for further processing. He uses Apache Kafka as a streaming platform and reads messages from Kafka, using Camel-K, a serverless version of the popular integration framework Apache Camel.